PROBLEMATIKA TENTANG PERKAWINAN YANG DILAKUKAN DENGAN SYARAT PALSU DI KUA BONTANG - Anggun Mulyasari (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTMarriages use administrative requirements counterfeit can be ratified by the court or in the term renewal of marriage, if the marriage has been performed according to religious requirements (valid according to religion) and that marriage has lasted a long time or they have to live like husband and wife, and they can show a deed registration of marriage made by an employee who is not authorized. Applicability of Marriage Law No. 1 of 1974 and its implementing regulations effectively in the community has been able to be accepted and implemented from October 1, 1975. Technically it is not a lot of obstacles, but if we look at their marriage cases that use a fake marriage certificate or requirements administrative false it is clear that the public has not implement government regulation of marriage and responsibility.